Consumersâ Attitude to the Protest Against Lady Gagaâs Concert: An Exploratory Study - Agus, Kresno (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2013)
Lady gaga is an American singer who has won 5 Grammy Awards. In the middle of 2012, she was requested to have concert in Jakarta with the contract value of tens billion. The concert was protested by a number of groups. The promoter had approached the pressure groups and negotiated the dressing.However, Lady Gagaâs management canceled the concert for security consideration.The objectives of the studyare:(1) to explore consumersâ attitude to the protest for the cancelation of Lady Gagaâs concert; and (2) using classical conditioning and expectancy-value theory, to explain consumersâ attitude to the protest.The study used focus group to collect data. The collected data was then transcribed and analyzed by content analysis.The results show that informantsâ opinions can be classified into two groups: agreement and disagreement with the protest for the cancelation of Lady Gagaâs concert. Informants either agree or disagree for some reasons. Classical conditioning theory can explain either consumerâs attitude. The difference is the object of consumersâ attitude who agreed was Lady Gaga herself, while the object of disagreement was the pressure group that sponsored the protest. The attitude of the disagreement can also be explained by expectancy-value theory.DOI :Â https://doi.org/10.21632/irjbs.6.3.149-169Keywords: Protest, Classical Conditioning Model, Expectancy-Value Theory, Focus Group, Qualitative Content Analysis